The Development of Bilingual Teaching Materials on Mathematical Logic Based on Integrated Mathematics - Riana, Riana; Ibrahim, Malik (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
This research aims to develop bilingual teaching materials mathematical logic integrated with Islamic religious values, to more easily convey mathematical materials with everyday life. This development research uses 4D models (define, design, devlop, disseminate). The subject of this study is student of university nahdlatul ulama west nusa tenggara. The instruments used are satisfaction questionnaires and validation questionnaires. Validity includes expert media validation, linguist validation, and validation of the substance of mathematical material. Research results based on expert validation include aspects of the feasibility of teaching materials getting a score of 91.5% with very decent criteria, and aspects of the validity of teaching materials reaching 210 with “highly valid” criteria, aspects of practicality of teaching materials reaching 90%. Based on these results, the bilingual teaching material integrated mathematical logic developed practically and validly for use.